REMASTERING SISTEM OPERASI ANDROID UNTUK PENINGKATAN PERFORMA MULTIMEDIAPADA LENOVO A859 - Rizqi Sukma Kharisma; Septian Nurwijaya (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
Smartphone is a communication tool that is often used as a means of accessing information. Nowadays many Smartphones that can be used to record voice, take a picture and make a video with good quality. On a Smartphone, there are a wide variety of operating systems such as Symbian, Blackberry, Android, and iOS.Android is a Linux-based operating system for mobile devices that open source. Android also has many versions such as Gingerbread, ICS, Jelly Bean, KitKat and the latest Lollipop. Not all samrtphone working optimally so harsher costum rom in order to maximize the ability of the smartphone.Remastering is a technique to change, add, delete application packages that are on an operating system. Remastering aims to make new android which has been optimized. The android operating system for multimedia can provide functionality to users especially in Lenovo A859 in increasing ability and creativity in multimedia